1996
DOI: 10.1093/ajhp/53.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hospital pharmacists’ job satisfaction and involvement in clinical activities

Abstract: Job satisfaction among hospital pharmacists employed by a national hospital pharmacy management company was measured by using a mail questionnaire. A previously validated survey that measured pharmacists’ job satisfaction was adapted for use in this study. Additional questions determined the pharmacist’s clinical pharmacy training and participation in clinical pharmacy services. Questionnaires were mailed to all full-time hospital pharmacists employed by the pharmacy management company. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 6 publications
5
27
2
1
Order By: Relevance
“…The results from this study are similar to those found by Olson and Lawson, 7 Kawabata et al, 8 and Cox and Fitzpatrick. 6 All results showed that job satisfaction was directly related to the number of clinical activities performed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results from this study are similar to those found by Olson and Lawson, 7 Kawabata et al, 8 and Cox and Fitzpatrick. 6 All results showed that job satisfaction was directly related to the number of clinical activities performed.…”
Section: Discussionsupporting
confidence: 92%
“…7,8 The tool most often used was developed by Barnett and Kimberlin (1986), 3 pharmacists' satisfaction with particular aspects of their work (a facet item) as well as their global job satisfaction without regard to any of these aspects (a facet-free item). In a study by Olson and Lawson (1996), 7 the relationship between hospital pharmacists' job satisfaction and involvement in clinical activities was explored by means of a questionnaire adapted from the Barnett and Kimberlin (1986) instrument. A significant but weak association (P < .001) was found between job satisfaction and the number of clinical activities reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Is it a reflection of a plunging job satisfaction rate in the community sector, or could this dissatisfaction reflect segments that are mired in distributive functions, while the profession undergoes growing pains of extending its clinical role? [27][28][29] Whether such blogs actually reflect the current state of practice anywhere is debatable, but it is certainly the picture painted if one reads many of the top blog posts. Recognizing that these types of outlets tend to disproportionately exhibit extreme views, it is still notable that so many pharmacist blogs represent unrest and are written with a combative voice.…”
Section: Discussionmentioning
confidence: 99%
“…One report indicated that mean job satisfaction increased as the time spent performing clinical duties increased. 5 Another report indicated that there was a positive relationship between job satisfaction and perceived utilization of skills and adequate staffing. 6 A recent white paper from the American College of Clinical Pharmacy identified work-life balance and favorable work schedules as important motivators for clinical pharmacists.…”
mentioning
confidence: 99%